1971
DOI: 10.1002/polc.5070340106
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of interfacial and surface tensions in polymer systems

Abstract: Princen's modification of Vonnegut's rotating drop procedure for measuring inter‐facial tension between low viscosity liquids has been adapted for use with pairs of liquid polymers with viscosities up to 5000 poise. Extrapolation to infinite time of results obtained with 10–20 min of rotation provided steady state data as indicated by its corre‐spondence with results reported from other techniques. An adaptation of this procedure was also found useful for determining surface tension values of molten polymers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Whatsoever, it is strongly reported that HDPE/EPDM blends are incompatible and immiscible . The well‐known limitation of immiscible polymer blends is that they are not thermodynamically stable . So they break easily initiating cracks due to coarseness on the micrometer scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatsoever, it is strongly reported that HDPE/EPDM blends are incompatible and immiscible . The well‐known limitation of immiscible polymer blends is that they are not thermodynamically stable . So they break easily initiating cracks due to coarseness on the micrometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a copolymer to immiscible polymers (A and B) where one part is miscible with polymer A, while the other part is miscible with polymer B is a successful method to bind two immiscible phases (A and B). It is believed that they reduce the blend interfacial tension and prevent coalescence …”
Section: Introductionmentioning
confidence: 99%
“…These methods include the pendant drop method, 4 -6 the sessile drop method, 7 and the spinning drop method. 8,9 These methods require an accurate measurement of the steady-state shape of the liquidliquid interface and the density difference. Because most polymer pairs have high viscosities, low interfacial tension values, and low density differences, the time to an equilibrium is very long, which leads to the thermal degradation of polymer melts and inaccurate interfacial tension value.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to demixed colloid polymer suspensions the interfacial properties in demixed polymer solutions [9,10,12,13] and in complex coacervates and their equilibrium liquid [11] have been studied. In these systems one finds typical values for the interfacial tension in the range 0-01-0.001 mN/m.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements have been done using the spinning drop technique [16][17][18]9] on a mixture of sterically stabilized silica and the polymer polydimethylsiloxane in cyclohexane.…”
Section: Introductionmentioning
confidence: 99%